2014
DOI: 10.1021/cs500911j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of Guaiacol over Ru(0001): A DFT Study

Abstract: The hydrodeoxygenation (HDO) of aromatic oxygenates over ruthenium was studied computationally on the model system guaiacol (2-methoxyphenol) on Ru(0001) using a DFT method. In addition to the adsorption geometries of the aromatic intermediates, the study focused on the energetics of elementary reaction steps that occur during the HDO of guaiacol. Bond scissions at the aliphatic side group were calculated to have barriers of at most 69 kJ mol −1 . In contrast, barriers for the cleavage of the aromatic bonds C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
122
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 82 publications
19
122
0
Order By: Relevance
“…It is also interesting to note that catechol formation was more prominent in HDO of guaiacol over Ru/C catalyst at 350 • C than at 400 • C, which was probably also related to temperature dependence of adsorption, namely low desorption of catechol at lower temperature [16]. According to a DFT study for Ru(0001) surface it was concluded that catecholate is formed prior to phenolate, finally yielding phenol as the main product [74]. .…”
Section: Kinetic Studies Elucidating the Reaction Pathways During Hdomentioning
confidence: 99%
See 1 more Smart Citation
“…It is also interesting to note that catechol formation was more prominent in HDO of guaiacol over Ru/C catalyst at 350 • C than at 400 • C, which was probably also related to temperature dependence of adsorption, namely low desorption of catechol at lower temperature [16]. According to a DFT study for Ru(0001) surface it was concluded that catecholate is formed prior to phenolate, finally yielding phenol as the main product [74]. .…”
Section: Kinetic Studies Elucidating the Reaction Pathways During Hdomentioning
confidence: 99%
“…In addition to kinetic studies, also adsorption studies [48], theoretical DFT (density function theory) calculations [22,[71][72][73][74][75] and bond dissociation energy calculations [36] have been performed.…”
Section: Reaction Pathways and The Thermodynamic Feasibility Of Diffementioning
confidence: 99%
“…In fact, Chiu et al 37 have investigated the guaiacol hydrodeoxygenation over Pt/C at 523 K and 623 K and low H 2 partial pressures of 0.4 bar. At the lower temperature, they observed primarily phenol (~50%), cyclohexanone (~10%), and cyclohexanol (~5%) as major reaction products, while at higher temperatures they observed primarily phenol (30%) and benzene (30%).…”
Section: Turnover Frequencies From Microkinetic Modelingmentioning
confidence: 99%
“…15,16 To gain insights into the reactivity of aromatic oxygenates on noble metal surfaces, many DFT studies have been performed and published. 13,[17][18][19][20][21][22][23][24] Honkela et al showed in particular that the dissociation of phenol into phenoxy was endothermic on Pt(111) and exothermic on Rh(111) and suggested that it may explain the higher propensity of Rh to deoxygenate aromatics. 19 Vlachos and co-workers recently proposed the first DFT-elucidated mechanism of guaiacol decomposition.…”
Section: Introductionmentioning
confidence: 99%